2018
DOI: 10.1056/nejmoa1800389
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prevention of Cardiovascular Disease with a Mediterranean Diet Supplemented with Extra-Virgin Olive Oil or Nuts

Abstract: In this study involving persons at high cardiovascular risk, the incidence of major cardiovascular events was lower among those assigned to a Mediterranean diet supplemented with extra-virgin olive oil or nuts than among those assigned to a reduced-fat diet. (Funded by Instituto de Salud Carlos III, Spanish Ministry of Health, and others; Current Controlled Trials number, ISRCTN35739639 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
1,623
3
50

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 2,446 publications
(1,857 citation statements)
references
References 31 publications
31
1,623
3
50
Order By: Relevance
“…While small phase II clinical trials, such as DASH-Sodium,40 have achieved these targets in the short term, they required complete control of dietary intake, which is impractical in free living populations. In contrast, the PREDIMED study,43 which promoted increased intake of potassium containing foods (fruit, vegetables, nuts) with greater adherence to the Mediterranean diet, without focusing on low sodium intake, reported a statistically significant reduction in cardiovascular disease and mortality, and adherence to a Mediterranean diet has an inconsistent correlation with sodium intake 4445. In addition, a recent analysis of the NHANES study reported that sodium intake >2.3 g/day was associated with better diet quality, compared with diets of less than 2.3 g/day, meaning that improving dietary quality is likely to be easier to achieve within a moderate sodium intake range 46.…”
Section: Discussionmentioning
confidence: 94%
“…While small phase II clinical trials, such as DASH-Sodium,40 have achieved these targets in the short term, they required complete control of dietary intake, which is impractical in free living populations. In contrast, the PREDIMED study,43 which promoted increased intake of potassium containing foods (fruit, vegetables, nuts) with greater adherence to the Mediterranean diet, without focusing on low sodium intake, reported a statistically significant reduction in cardiovascular disease and mortality, and adherence to a Mediterranean diet has an inconsistent correlation with sodium intake 4445. In addition, a recent analysis of the NHANES study reported that sodium intake >2.3 g/day was associated with better diet quality, compared with diets of less than 2.3 g/day, meaning that improving dietary quality is likely to be easier to achieve within a moderate sodium intake range 46.…”
Section: Discussionmentioning
confidence: 94%
“…Feeding mice with a high‐fibre diet increased the abundance of acetate‐producing gut bacteria, which significantly decreased myocardial hypertrophy and fibrosis (Marques, et al , ). Furthermore, a Mediterranean diet resulted in low TMAO levels, which can consequently prevent cardiovascular consequences and HF (Papadaki, et al , ; Estruch, et al , ). One study specifically demonstrated that ginger supplementation modulated the gut microbiota community, inducing a significant increase in fatty acid metabolism (Wang, et al , ).…”
Section: Gut Microbiota Interventions For Cvdmentioning
confidence: 99%
“…41 Finally, study participants were mainly white men, limiting generalizability. The study duration might have been too short for postulated effects on endothelial function and graft fibrosis to translate into improved renal function.…”
mentioning
confidence: 99%